2005
DOI: 10.1007/s10722-005-0001-1
|View full text |Cite
|
Sign up to set email alerts
|

Promising genetic resources for resistance to wheat streak mosaic virus and the wheat curl mite in wheat-Thinopyrum partial amphiploids and their derivatives

Abstract: Wheat streak mosaic virus (WSMV), vectored by the wheat curl mite (WCM), Aceria tosichella Keifer, is one of the most destructive viral diseases of wheat found in many wheat producing areas of the world. Host resistance is the most effective method for controlling this disease and its vector. Symptomatological analysis and enzymelinked immunosorbent assay (ELISA) were used to characterize WSMV-resistance in wheat-alien partial amphiploid lines and their derivatives. The results showed that most of partial amph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…Recently, it was reported that the wheat-Th. intermedium partial amphiploid MT-2 was resistant not only to WSMV and WCM , but also to eyespot and Cephalosporium stripe (Cox et al, 2002;Li et al, 2003b).…”
Section: Thinopyrum and Its Contribution In Wheat Improvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that the wheat-Th. intermedium partial amphiploid MT-2 was resistant not only to WSMV and WCM , but also to eyespot and Cephalosporium stripe (Cox et al, 2002;Li et al, 2003b).…”
Section: Thinopyrum and Its Contribution In Wheat Improvementmentioning
confidence: 99%
“…Resistance to the WCM in lines derived from Agrotana, which is immune to WSMV, is controlled by two Th. ponticum J S chromosomes (Chen et al, 1999a;Li et al, 2003b). Recently, the resistance to common root rot (Cochliobolus sativus [Ito and Kurib] Drechs.…”
Section: J S Genome Chromosomes and Their Linkages With Disease And Mmentioning
confidence: 99%
“…In addition, it was shown, like for other diseases, that Th. intermedium is a valuable source for introducing mite and WSMV resistance into wheat (Friebe et al., 1996; Cox et al., 2002; Li et al., 2004) and molecular markers specific for these introgressions have been developed (Chen et al., 1998a,b, 1999, 2003). In addition, two temperature‐sensitive resistances to WSMV have been recently described by Seifers et al.…”
Section: Sources and Genetics Of Resistance/tolerancementioning
confidence: 99%
“…Great attention has been also paid to the discovery and breeding of WSMV-and WCM-resistant wheat varieties as a promising methods for controlling this mite-vectored disease (e.g. Chen et al 2003;Malik et al 2003;Thomas et al 2004;Harvey et al 2005;Li et al 2005Li et al , 2007. Aceria tosichella has been identified as a vector of three other plant disease viruses, namely Brome Streak Mosaic Virus (Stephan et al 2008), Triticum Mosaic Virus (Seifers et al 2009), and High Plain Disease (Mahmood et al 1998;Seifers et al 2002;Skare et al 2003Skare et al , 2006.…”
Section: Virus Vectoringmentioning
confidence: 99%